Medieval cities : their origins and the revival of trade - Pirenne, Henri, 1862-1935 (Princeton classics., 2014)
Nearly a century after it was first published in 1925, Medieval Cities remains one of the most provocative works of medieval history ever written. This book argues that it was not the invasion of the Germanic tribes that destroyed the civilization of antiquity, but rather the closing of Mediterranean trade by Arab conquest in the seventh century.